The Molecular Pathways of Pyroptosis in Atherosclerosis - Song, Dan; Li, Manman; Yu, Xue; Wang, Yuqin; Fan, Jiaying; Yang, Wei; Yang, Liming; Li, Hong (Frontiers in Cell and Developmental Biology, 2022)
Atherosclerosis (AS) is a chronic inflammatory disease seriously endangering human health, whose occurrence and development is related to many factors. Pyroptosis is a recently identified novel programmed cell death associated with an inflammatory response and involved in the formation and progression of AS by activating different signaling pathways. Protein modifications of the sirtuin family and microRNAs (miRNAs) can directly or indirectly affect pyroptosis-related molecules. It is important to link atherosclerosis, thermogenesis and molecular modifications. This article will systematically review the molecular pathways of pyroptosis in AS, which can provide a new perspective for AS prevention and treatment.